Modeling of Indoor Air Flow Distribution in a Naturally Ventilated Kitchen - Sapkota, Buddhi P.; Uprety, Kedar N.; Khanal, Harihar; Bhave, Prakash V. (The Nepali Mathematical Sciences Report, 2016)
This paper focuses on the modeling of indoor air pollution in a naturally ventilated kitchen based on the computational fluid dynamics (CFD) approach to assess its ventilation effectiveness. The 3D incompressible Navier-Stokes equations with conservation of total energy are solved numerically using ANSYS-Fluent software and the pollutant paths are investigated from the profiles of velocity, pressure, turbulent kinetic energy and temperature throughout different sections of the kitchen. Experimental verification is made through the measurement of indoor air contaminant in the same kitchen. The simulation results agree well with the on-site measured data.